Single and double box HMGB proteins differentially destabilize nucleosomes. Issue 2 (16th November 2018) - McCauley, Micah J; Huo, Ran; Becker, Nicole; Holte, Molly Nelson; Muthurajan, Uma M; Rouzina, Ioulia; Luger, Karolin; Maher, L James; Israeloff, Nathan E; Williams, Mark C
Abstract: Nucleosome disruption plays a key role in many nuclear processes including transcription, DNA repair and recombination. Here we combine atomic force microscopy (AFM) and optical tweezers (OT) experiments to show that high mobility group B (HMGB) proteins strongly disrupt nucleosomes, revealing a new mechanism for regulation of chromatin accessibility. We find that both the double box yeast Hmo1 and the single box yeast Nhp6A display strong binding preferences for nucleosomes over linker DNA, and both HMGB proteins destabilize and unwind DNA from the H2A–H2B dimers. However, unlike Nhp6A, Hmo1 also releases half of the DNA held by the (H3–H4)2 tetramer. This difference in nucleosome destabilization may explain why Nhp6A and Hmo1 function at different genomic sites. Hmo1 is enriched at highly transcribed ribosomal genes, known to be depleted of histones. In contrast, Nhp6A is found across euchromatin, pointing to a significant difference in cellular function.